Gender and gender typicality in autobiographical memory: A replication and extension. Issue 2 (7th February 2018) - Grysman, Azriel
ABSTRACT: Gender differences in autobiographical memory (AM) are commonly reported, but often inconsistent across studies using varied measurement techniques. The current study aimed to provide more clarity to where and why gender differences emerge by carefully controlling for factors hypothesised to be relevant to gender; thus, it tested shorter and longer term AM using both narrative and questionnaire measures, and further tested whether subscription to feminine-typical traits mediated these differences. Results demonstrate that women's memory narratives score higher than men's on measures of affect, connection to others, factual and interpretive elaboration, and thematic coherence. Women scoring high on feminine-typical traits demonstrated larger differences when compared to men scoring low on these measures than did average men and women, but these latter groups still differed substantially. Gender differences were present in narrative measures of longer term events (often more than two years) and shorter term events (one day–one week), but effect sizes were larger in longer term events. Gender differences were not common on questionnaire measures. These findings replicate previous narrative-based gender differences and highlight the need for carefully constructed studies of socio-cultural, individual, and developmental influences.